43‐1: Tri‐stable Cholesteric Liquid Crystal Smart Window. Issue 1 (30th May 2018) - Li, Cheng-Chang; Tseng, Heng-Yi; Chen, Chun-Wei; Wang, Chun-Ta; Jau, Hung-Chang; Wu, Yu-Ching; Hsu, Wen-Hao; Lin, Tsung-Hsien
Abstract : This work demonstrated a tri‐stable cholesteric liquid crystal (CLC) with multi‐electrode driving. Compare to previous device, the tri‐stable CLC can be switched between transparent, absorption and scattering state, giving rise to the applications in multi‐function, multi‐stable smart windows.